Inflammatory Biomarkers in Elite Cross-Country Skiers After a Competition Season: A Case–Control Study - Luoto Raakel; Ruuskanen Olli; Ihalainen Johanna K.; Pekkala Satu; Hintikka Jukka; Kanerva Noora; Waris Matti; Heinonen Olli J.; Valtonen Maarit (Springer, 2025)
Purpose
Whether elite athletes, who have been exposed to vigorous-intensity exercise combined with other stressors, have elevated systemic low-grade inflammation, remains largely unclear. To address this question, we studied the levels of six inflammatory cytokines as potential biomarkers of a low-grade inflammatory state in elite athletes after an 11-month training and competition season.
Methods
We collected sera from 27 Finnish elite cross-country skiers and 27 gender- and age-matched, moderately-exercising controls. The serum concentrations of C-reactive protein (CRP), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), glycoprotein acetyls (GlycA), interleukin 10 (IL-10), and interferon gamma (IFN-γ) cytokines were quantified as surrogate markers of low-grade inflammation.
Results
The athletes were found to have significantly lower concentrations of CRP (P = 0.0232) and higher concentrations of IL-10, TNF-α, and IFN-γ (P = 0.0097, P = 0.0256, and P = 0.0185, respectively) than the controls. No significant differences between athletes and controls were detected in the concentrations of IL-6 and GlycA. The inflammatory score (IS) did not differ significantly between athletes and controls.
Conclusion
The results of this study argued against the hypothesis of a significant chronic low-grade inflammation in response to prolonged high-performance exercise among elite endurance athletes.